Forecasting Pendapatan UMKM: Strategi Tiga UMKM Unggulan di Kalurahan Hargorejo Dalam Kontribusi Terhadap Kalurahan Hargorejo, Kapanewon Kokap Kulon Progo Menggunakan Metode Arima - Thoriq Afris Suryono, Muhammad; Tania Aulia, Rose; Novtaputri, Elizabeth; Bakhtiar, Riyan (CV. Lafadz Jaya, 2023)
This research aims to forecast the income of MSMEs (Micro, Small and Medium Enterprises), namely Batik Ngudi Rejeki, Geblek Mbak Yuni, and Better Snack in Hargorejo Village, Kapanewon Kokap, Kulon Progo using the ARIMA (AutoRegressive Integrated Moving Average) method. MSME income data from 2019 to 2022 is used in this analysis. The ARIMA method is used to identify patterns and trends in revenue data, as well as predict future earnings. The results of the ARIMA analysis show forecasting the income of MSMEs Batik Ngudi Rejeki, Geblek Mbak Yuni, and Better Snack in the contribution of the Hargorejo, Kokap, Kulon Progo Villages for the 2023 period. The results of this forecasting can provide insight into the development of MSME income in the future and become a reference for business owners in more effective business planning, decision making, and strategy development. The data used is historical data on MSME income in a time series, where the process is analyzed using statistical software Eviews 12 to produce an accurate forecasting model.